Penguatan Ekosistem Dukungan Menyusui melalui Edukasi Gizi dan Kesehatan pada Festival Menyusui Bareng, Yogyakarta - Rizky Triutami Sukarno; Azizah Nurlitasari Tambulana; Joko Murdiyanto; Rahmi Sofya; Leny Fitra Sari (FKM UIN Sumatera Utara Medan, 2025)
This community service activity was carried out as part of the “Breastfeeding Together Festival” with the theme “Breastfeeding is a Journey, Let's Accompany Mothers,” organized by the Faculty of Medicine, Universitas ‘Aisyiyah Yogyakarta, in collaboration with the Indonesian Breastfeeding Mothers Association (AIMI) Yogyakarta. The program aimed to strengthen maternal and child health promotion through collaboration among academia, local government, and community organizations. This descriptive study utilized secondary data from onsite health examinations and questionnaires (n = 20 mother-child dyads) to describe maternal-child nutritional and health profiles and identify family support patterns related to exclusive breastfeeding. A participatory approach was employed through interactive education sessions, lactation counseling, and basic health assessments. Most children had normal weight-for-length/height Z-scores (80% within −2 to +2 SD; 20% overweight), and 80% had normal head circumference. All mothers had a mid-upper arm circumference ≥ 23.5 cm, indicating no chronic energy deficiency, although 65% were overweight or obese and 15% had prehypertension or hypertension. Family and social support were high (spousal support 90%; maternal grandparents 65%), and the prevalence of exclusive breastfeeding reached 90%. These findings underscore the importance of integrating postpartum monitoring and targeted lactation counseling with maternal-child health screening, including nutrition education, portion control, and safe physical activity, within primary care. Future initiatives should expand digital education, routine maternal-child health monitoring, and community-based lactation support networks to strengthen a sustainable ecosystem for breastfeeding mothers.